COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN DANA DESA DI DESA CEMAGA UTARA KECAMATAN BUNGURAN SELATAN KABUPATEN NATUNA - Huzaini, Ahmad; Herdiana, Dian; Mujtahid, Iqbal Miftakhul (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Collaborative governance is one of the ideal techniques in an attempt to enhance the quality of government administration, public services, and public policy performance in the middle of government limits in terms of resource capacity, financing sources, and networks. The goal of this research was to analyze government cooperation linked to the administration of village finances in Cemaga Utara Village, Natuna Regency during the COVID-19 epidemic. The research technique employed in this study is a qualitative method with a descriptive approach. In this study, researchers utilized primary data and secondary data. Based on the findings of the study that collaborative governance in managing village finances in Cemaga Utara Village, Natuna Regency has been operating very successfully by evaluating numerous components; beginning conditions, collaborative process, facilitative leadership and institutional design. The findings of the research also demonstrate that the characteristics that limit the collaborative process still exist in coordination indicators, namely that face-to-face meetings or dialogues are not optimal in the COVID-19 situation to maximaze the activites